Democracy, institution, market: the conflicting winds of mediation - Jacques Faget (Oñati Socio-Legal Series)
The considerable development of mediations over the past few decades in Western countries is correlated with the insufficiencies and anachronism of institutional and social regulations knocked over by postmodernity. The metamorphoses generated by their success are not without struggle between jurists weakened by the crisis of legal rationality, defending their monopoly, and the new professionals of mediation coming from social sciences. Thus, two conceptions of mediation confront one another, an idealistic vision of empowerment and emancipation of individuals, and a pragmatic or marketably vision that tends to juridicize alternatives dispute resolution.